Soil management and soil properties in a Kenyan smallholder irrigation system on naturally low-fertile soils. (January 2018) - Caretta, Martina Angela; Westerberg, Lars-Ove; Mburu, David Mwehia; Fischer, Manuel; Börjeson, Lowe
Abstract: In this study we examine the impact of soil management practices on soil properties in a landscape with naturally relatively poor soils on and below the dry slopes of a Rift Valley escarpment in Kenya that have been dominated by extensive smallholder investments in canal irrigation over the last 300 years. We show that farmers in the area have been able to keep up agricultural production in the face of growing population. The actual practices of soil management at one moment in time appear to be of minor importance to soil improvement, as indicated by the low correlation between Soil Management Index (SMI) and soil chemical data. However, cultivation triggers a process of slow soil improvement manifested by a positive correlation between nutrient levels and duration of irrigated cultivation and soil management, which likely explains farmers' confidence in soil productivity. However, we also identify sodicity as a risk connected to intensified irrigation in the area. Finally, we stress the need for further studies integrating investigations of local irrigation and soil management with soil and water quality analyses. These will be crucial to shape sustainable place-based and farmer-led solutions for African agricultural growth. Highlights: We study soil management practices on soil properties in relatively poor soils. This Rift Valley escarpment has been dominated by extensive smallholder investments. Farmers have kept up agricultural production in the face of growing population. Cultivation triggers a process of slow soil improvement. Sodicity is a risk connected to intensified irrigation in the area.